Normalization of serum B‐cell maturation antigen levels predicts overall survival among multiple myeloma patients starting treatment. (22nd May 2020) - Jew, Scott; Chang, Tiffany; Bujarski, Sean; Soof, Camilia; Chen, Haiming; Safaie, Tahmineh; Li, Mingjie; Sanchez, Eric; Wang, Cathy; Spektor, Tanya M.; Emamy‐Sadr, Marsiye; Swift, Regina; et al.
Summary: Serum B‐cell maturation antigen (sBCMA) is a novel biomarker for B‐cell malignancies. A normal reference range (<82·59 ng/ml) has been recently established but the impact of achieving normal levels to outcomes for patients receiving treatment for B‐cell malignancies has not been studied. We first found that among multiple myeloma (MM) patients starting a new treatment, those who begin treatment within normal sBCMA limits (<82·59 ng/ml) have improved progression‐free survival (PFS; P = 0·0398) and overall survival (OS; P = 0·0217) than those who do not. Furthermore, among patients who begin treatment with elevated (≥82·59 ng/ml) sBCMA levels, we assessed the relationship of a decrease in sBCMA to the normal range to OS and found that those who normalize sBCMA demonstrated improved OS ( P = 0·0078). Normalizing patients also experienced a markedly improved overall response rate ( P < 0·0001). Moreover, all patients who achieved complete remission (CR) showed normalization of sBCMA, and time to normalization (median 0·9 months) was faster than time to CR (5·0 months; P = 0·0036) for these patients. These results suggest that normalization of sBCMA may be an accurate predictor of OS for MM patients during treatment and predict for a higher likelihood of response.